The Oxford-Dartmouth Thirty Degree Survey I: Observations and Calibration of a Wide-Field Multi-Band Survey - MacDonald, E; Allen, P; Dalton, G; Moustakas, L; Heymans, C; Edmondson, E; Blake, C; Clewley, L; Hammell, M; Olding, E; Miller, L; Rawlings, S; et al. (2004)
The Oxford Dartmouth Thirty Degree Survey (ODTS) is a deep, wide, multi-band imaging survey designed to cover a total of 30 square degrees in BVRi'Z, with a subset of U and K band data, in four separate fields of 5-10 deg^2 centred at 00:18:24 +34:52, 09:09:45 +40:50, 13:40:00 +02:30 and 16:39:30 +45:24. Observations have been made using the Wide Field Camera on the 2.5-m Isaac Newton Telescope in La Palma to average limiting depths (5 sigma Vega, aperture magnitudes) of U=24.8, B=25.6, V=25.0, R=24.6, and i'=23.5, with observations taken in ideal conditions reaching the target depths of U=25.3, B=26.2, V=25.7, R=25.4, and i'=24.6. The INT Z band data was found to be severely effected by fringing and, consequently, is now being obtained at the MDM observatory in Arizona. A complementary K-band survey has also been carried out at MDM, reaching an average depth of K_{5σ}~18.5. At present, approximately 23 deg^2 of the ODTS have been observed, with 3.5 deg^2 of the K band survey completed. This paper details the survey goals, field selection, observation strategy and data reduction procedure, focusing on the photometric calibration and catalogue construction. Preliminary photometric redshifts have been obtained for a subsample of the objects with R <= 23. These results are presented alongside a brief description of the photometric redshift determination technique used. The median redshift of the survey is estimated to be z~0.7 from a combination of the ODTS photometric redshifts and comparison with the redshift distributions of other surveys. Finally, galaxy number counts for the ODTS are presented which are found to be in excellent agreement with previous studies.